Theoretical and Practical Dimensions of Translating Specialized Terminology: A Linguistic and Cultural Approach - Iroda, Ortikova (The Lingua Spectrum, 2025)
This article investigates the theoretical and practical dimensions of translating specialized terminology across scientific, technical, and cultural domains. Terminology forms the backbone of professional discourse by encapsulating complex concepts into precise lexical units; however, its translation often presents challenges that surpass ordinary language transfer. The study highlights how structural differences between languages, conceptual gaps, and culture-bound references complicate the search for semantic equivalence. Drawing on the works of Sager, Felber, L’Homme, and other scholars, the paper examines key translation issues such as polysemy, non-equivalence, morpho-syntactic incompatibility, and ideological or metaphorical load. It discusses strategies – including borrowing, calquing, descriptive translation, neologism, and cultural substitution – that enable translators to achieve both linguistic fidelity and communicative adequacy. Practical examples from medicine, law, and information technology illustrate the importance of domain knowledge, cultural sensitivity, and institutional standardization. The article argues that successful terminology translation requires interdisciplinary collaboration among linguists, subject-matter experts, and policymakers to ensure conceptual clarity, cross-cultural accessibility, and global knowledge exchange.